Patrimoni e protocolli: i beni culturali immateriali tra valori globali e pratiche locali come terreno di conflitto e di mediazione - Letizia Bindi (EtnoAntropologia)
Intangible cultural heritage increasingly becomes a conflict/mediation field among different issues and global/local hierarchies of value. Here the author outlines the first results of an ethnography in South-Central Italy about a group of ceremonials involving animals, recently questioned by animal rights movement associations for suspected mistreatment and its very recent legal solution.